«URALKHIMPLAST – HÜTTENES ALBERTUS.» NEW PARTNERSHIP – A BIG STEP FORWARD - article editotial (Литьë и металлургия)
Interview  with  top  managers  of  HÜTTENES  ALBERTUS  and  UCP  CHEMICALS («URALKHIMPLAST»): Carsten Kuhlgatz, Klaus Pampel, Norbert Wieser, Alexander E. Gerdt